ANALISIS LAPORAN KEUANGAN SEBAGAI DASAR PENILAIAN KINERJA PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2016 - Pasiakan, Melisa Patricia Novelina; Alexander, Stanly W.; Pangerapan, Sonny (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Companys financial performance can be known from the aspect of financial ratios, such as Liquidity, Solvency, Profitability, and Activity ratios. The development of a company, can be seen and can be compared through the companys financial performance. This is certainly useful for investors, creditors, and owners to make profitable investment decisions. This study aims to assess the financial performance of PT. Semen Indonesia Tbk, PT. Indocement Tunggal PrakasaTbk, and PT HolcimIndonesia by using financial ratio analysis. This study uses secondary data from Indonesia Stock Exchange. The result of research shows there are differences of financial performance between PT. Semen Indonesia Tbk, PT. Indocement Tunggal PrakasaTbk, and PT Holcim Indonesia. Suggestions for the Management Party should further improve the performance of total asset management, so that efficient corporate finance will be better.Keywords: Liquidity, Solvency, Profitability, Activity, and Financial Performance